An ICT strategy for the sustainable development of the tourism sector in a developing country: a case study of Zimbabwe - Tsokota, Theo; Solms, Rossouw von; Greunen, Darelle van (John Wiley & Sons, 2019)
This research has sought to propose a strategy for the sustainable use of ICT in the tourism sector in Zimbabwe. In order to achieve the above‐mentioned objective, this research, which is a comprehensive case study into the tourism sector of Zimbabwe, has deployed semi‐structured interviews, questionnaires, observations and netnograghy to collect the data. The case study was carried out, in accordance with the case study guidelines, as outlined by Yin, and guided by the interpretive paradigm. After a further analysis of the results, the results that pointed to the same aspect were grouped together; and various deductions were made, as a diagnosis of the identified problem. The identified problems were synthesised into seven diagnostics. A guiding policy was then identified for each of the diagnostics, leading to a set of coherent actions, derived from each of the identified guiding policies. The research also showed the implementation of the coherent set of actions that consist of three layers. These are: government, regulator and service providers. This research contributes to ICT4D literature; and it has provided an ICT strategy for sustainable development in the tourism sector for appropriate interventions from government and other role‐players in the tourism sector.